Anew species of cellaria (Bryozoa, Cheilostomatida) from the late dDanian (Paleocene) of Patagonia (Argentina) - López Gappa, Juan José (2025)
The cheilostome bryozoan genus Cellaria is characterized by articulated, dichotomously branching colonies, which are composed of cylindrical internodes joined by cuticular nodes. The genus includes over 130 species, with approximately 70 taxa ranging from the late Paleocene to the Holocene. This study describes Cellaria daniana sp. nov., based on material collected from the Roca Formation, upper Danian (Paleocene) of northern Patagonia, Argentina, making it the earliest known occurrence of the genus. The most distinctive feature of C. daniana sp. nov. is its vicarious avicularium, which lacks mandibular pivots and exhibits a distally depressed cryptocyst, resembling that of C. stachi from the Eocene of Victoria, Australia. Cellaria stachi shows a great morphological similarity with C. daniana sp. nov., supporting a close biogeographic connection between South America and Australasia during the Early Cenozoic.